Composite film for manufacturing container liquid bag and preparation process

By grafting phenyl-POSS onto the surface of montmorillonite to functionalize polyethylene and polypropylene, a high-strength organic-inorganic hybrid filler was prepared, which solved the problem of insufficient strength of liquid bags. The prepared composite film can effectively prevent breakage during transportation and meets national standards.

CN120921788AActive Publication Date: 2025-11-11SUZHOU ZIJIN PLASTIC

Patent Information

Application Number
CN202511453331.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-13
Publication Date
2025-11-11
Estimated Expiration
2045-10-13

AI Technical Summary

Technical Problem

Existing disposable container liquid bags are not strong enough during transportation and are easily scratched or torn, leading to leakage of packaged products. Furthermore, the effect of using montmorillonite to reinforce the mechanical strength of polyethylene inner bags in existing technologies is limited.

Method used

By grafting phenyl-POSS-functionalized polyethylene and phenyl-POSS-functionalized polypropylene onto the surface of alkenyl-functionalized montmorillonite with stable interlaminar spacing through the Friedel-Crafts alkylation reaction mechanism, a high-strength organic-inorganic hybrid filler was prepared. The composite film was then prepared using an eleven-layer co-extrusion blow molding process, meeting the TB/T 2689.4-2018 standard.

Benefits of technology

The prepared composite film has significantly improved mechanical and barrier properties, meets national standards, has practical application value, and can effectively prevent liquid bags from breaking due to violent shaking during transportation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120921788A_ABST
    Figure CN120921788A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of research and development of container liquid bag materials, and discloses a composite film for manufacturing a container liquid bag and a preparation process of the composite film, specifically, on the basis of a Friedel-Crafts alkylation reaction mechanism, phenyl-POSS functional polyethylene and phenyl-POSS functional polypropylene are grafted on the surface of alkenyl functional interlamellar spacing stable montmorillonite, and the composite film is prepared through the following steps: grafting phenyl-POSS functional polyethylene and phenyl-POSS functional polypropylene on the surface of alkenyl functional interlamellar spacing stable montmorillonite; the organic and inorganic hybrid high-strength filler used for modifying the polyolefin matrix is prepared by using the organic and inorganic hybrid high-strength filler, the composite film is prepared through an eleven-layer co-extrusion blow molding process, and the film product meets the technical requirements specified in the standard of TB / T 2689.4-2018 Part 4 of Railway Cargo Containerization Transport: Disposable Container Liquid Container Bag, and can be used as an inner bag material of a disposable Container Liquid Bag.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of container liquid bag material research and development technology, specifically to composite films used in manufacturing container liquid bags and their preparation processes. Background Technology

[0002] Container liquid bags are flexible containers used for storing and transporting non-hazardous, atmospheric pressure liquid chemicals or food. Disposable liquid bags not only avoid cross-contamination of materials but also reduce the cost of cleaning the liquid bags.

[0003] Currently, the product structure of disposable container liquid bags is usually a single outer bag (made of polypropylene woven fabric) and three or more inner bags (made of single or multiple co-extruded polyethylene film). These liquid bags have the advantage of low cost, but they also have the disadvantage of insufficient strength. In particular, they are unable to withstand the impact of the liquid sloshing caused by the violent shaking of the internal liquid during transportation. They are also very easy to be scratched or torn during loading and unloading, which brings the risk of leakage of the packaged products.

[0004] There are existing reports of using montmorillonite as a filler to enhance the mechanical strength of polyethylene inner bags. Montmorillonite is widely available and inexpensive, and can significantly improve the rigidity, strength, and barrier properties of polyethylene even at low addition levels. Summary of the Invention

[0005] This invention is based on the Friedel-Crafts alkylation reaction mechanism. Phenyl-POSS functionalized polyethylene and phenyl-POSS functionalized polypropylene are grafted onto the surface of alkenyl functionalized interlaminar spacing-stabilized montmorillonite to obtain an organic-inorganic hybrid high-strength filler for modifying polyolefin matrices. A composite film is then produced through an eleven-layer co-extrusion blow molding process. This film product meets the technical requirements specified in TB / T 2689.4-2018 "Railway Freight Containerized Transport Part 4: Disposable Container Liquid Bags" standard and can be used as the inner bag material for disposable container liquid bags.

[0006] The composite film used to manufacture container liquid bags has the following product structure: LDPE layer / TIE layer / PP layer / TIE layer / PP-PE functional layer / TIE layer / PP-PE functional layer / TIE layer / PP layer / TIE layer / m-LLDPE layer; The LDPE layer is formulated with 100wt% low-density polyethylene resin, and the amount used is 5-15 parts by weight. The TIE layer is formulated with 100wt% maleic anhydride-grafted polyethylene resin, and the dosage is 1-5 parts by weight. The PP layer is formulated with 100wt% polypropylene resin, and the dosage is 5-15 parts by weight. The PP-PE functional layer is formulated with 30-50 wt% low-density polyethylene resin and 50-70 wt% organic-inorganic hybrid high-strength filler, with a dosage of 15-25 parts by weight. The formulation of the organic-inorganic hybrid high-strength filler is as follows: 20-30 wt% phenyl-POSS functionalized polyethylene, 20-30 wt% phenyl-POSS functionalized polypropylene, and 40-60 wt% alkenyl functionalized interlamellar spacing stabilizing montmorillonite; wherein, the phenyl-POSS functionalized polyethylene is obtained by grafting monoalkenyl phenyl-POSS onto the polyethylene backbone via a free radical addition reaction; the phenyl-POSS functionalized polypropylene is obtained by grafting monoalkenyl phenyl-POSS onto the polypropylene backbone via a free radical addition reaction; and the alkenyl functionalized interlamellar spacing stabilizing montmorillonite is obtained by intercalating sodium-based montmorillonite with alkenylated gemini quaternary ammonium salt via an ion exchange reaction. The m-LLDPE layer is formulated with 100wt% metallocene polyethylene resin, and the amount used is 5-15 parts by weight.

[0007] Preferably, the thickness of the composite film is 130-180 μm.

[0008] Preferably, the mass ratio of alkenylated gemini quaternary ammonium salt to sodium-based montmorillonite in the alkenylated functionalized interlamellar spacing stabilized montmorillonite is 1:(3-8).

[0009] Preferably, the sodium-based montmorillonite has a sheet diameter of 3-8 μm and a thickness of 5-15 nm.

[0010] Preferably, the mass ratio of monoalkenylphenyl-POSS to polyethylene in the phenyl-POSS functionalized polyethylene is 1:(8-10); Preferably, the mass ratio of monoalkenylphenyl-POSS to polypropylene in the phenyl-POSS functionalized polypropylene is 1:(8-10).

[0011] The process for preparing the composite film used in manufacturing container liquid bags includes the following steps: Step 1: Synthesize monoalkenylphenyl-POSS, and then use monoalkenylphenyl-POSS to functionalize and modify polyethylene and polypropylene in sequence to obtain phenyl-POSS-functionalized polyethylene and phenyl-POSS-functionalized polypropylene. Alkenylated gemini quaternary ammonium salts were synthesized, and sodium-based montmorillonite was functionalized by the alkenylated gemini quaternary ammonium salts to obtain alkenylated functionalized interlamellar spacing stabilized montmorillonite. Under the action of Lewis acid, the phenyl functional groups in phenyl-POSS functionalized polyethylene and phenyl-POSS functionalized polypropylene undergo Friedel-Crafts alkylation reaction with the alkenyl functional groups on the surface of alkenyl functionalized interlaminar spacing stabilized montmorillonite, and polyethylene and polypropylene are grafted onto the surface of montmorillonite to obtain an organic-inorganic hybrid high-strength filler. Step 2: Prepare the materials according to the formula of the composite film. Put the raw materials of each layer into the hoppers of the eleven screw extruders of the eleven-layer co-extrusion film blow molding unit. The molten resin is combined at the die head through the distributor, extruded and blown by the die head, cooled and wound up to prepare the composite film for manufacturing container liquid bags.

[0012] Preferably, the preparation method of the alkenylated gemini quaternary ammonium salt is as follows: The amino-enyl addition reaction occurs through the amino functional group of 3-amino-1-propanol and the alkenyl functional group of methacryloyloxyethyltrimethylammonium chloride, and the molar ratio of 3-amino-1-propanol to methacryloyloxyethyltrimethylammonium chloride is controlled to be 1:2.05-2.09 to generate hydroxyammonium chloride monomer. A nucleophilic substitution reaction is carried out between the hydroxyl functional group of ammonium hydroxychloride monomer and the acyl chloride functional group of 10-undecenoyl chloride, and the molar ratio of ammonium hydroxychloride monomer to 10-undecenoyl chloride is controlled to be 1:1.01-1.05 to generate an alkenylated gemini quaternary ammonium salt.

[0013] Preferably, the method for preparing the monoalkenylphenyl-POSS is as follows: Under the action of Lewis acid, Friedel-Crafts alkylation reaction occurs through the alkenyl functional group of 10-undecenol and the phenyl functional group of octaphenyl-POSS, and the molar ratio of octaphenyl-POSS to 10-undecenol is controlled to be 1:0.91-0.95 to generate monohydroxyphenyl-POSS; Under the action of sulfate, the hydroxyl functional group of monohydroxyphenyl-POSS undergoes a dehydration elimination reaction to generate monoalkenylphenyl-POSS.

[0014] Preferably, the Lewis acid is one of aluminum trichloride, ferric trichloride, tin tetrachloride, and zinc dichloride.

[0015] Preferably, the sulfate is one of aluminum sulfate, zirconium sulfate, and potassium bisulfate.

[0016] Beneficial effects Based on molecular design mechanisms, this invention first reacts 3-amino-1-propanol with methacryloyloxyethyltrimethylammonium chloride via an amino-enyl addition reaction, and then reacts with 10-undecenoyl chloride via a nucleophilic substitution reaction to obtain an alkenylated gemini-type quaternary ammonium salt. Using this salt as an intercalating agent, sodium-based montmorillonite is intercalated and modified via an ion exchange reaction to obtain alkenylated functionalized interlamellar spacing stabilized montmorillonite. Using octaphenyl-POSS and 10-undecenol as raw materials, a Friedel-Crafts alkylation reaction of phenyl-alkenyl groups was first carried out, followed by a hydroxyl dehydration elimination reaction to obtain monoalkenylphenyl-POSS. Then, under the action of a free radical initiator, monoalkenylphenyl-POSS was grafted onto the main chain of polyethylene or polypropylene through a free radical addition reaction to obtain phenyl-POSS functionalized polyethylene or phenyl-POSS functionalized polypropylene. Based on the Friedel-Crafts alkylation reaction mechanism, using phenyl-POSS functionalized polyethylene, phenyl-POSS functionalized polypropylene and alkenyl functionalized interlaminar spacing stabilizing montmorillonite as raw materials, an organic-inorganic hybrid high-strength filler for modifying polyolefin matrices was prepared. Finally, an eleven-layer co-extrusion blow molding process was used to produce a high-performance composite film. Its mechanical properties meet the standards of TB / T2689.4-2018 "Railway Freight Containerization Transport Part 4: Disposable Container Liquid Bags" and have excellent comprehensive performance, making it valuable for practical applications. Attached Figure Description

[0017] Figure 1 The results of puncture resistance tests for composite films used in the manufacture of container liquid bags; Figure 2 The 1H NMR spectrum of monoalkenylphenyl-POSS; Figure 3 The 1H NMR spectrum of the alkenylated gemini quaternary ammonium salt is shown. Detailed Implementation

[0018] The main raw materials used in this invention are as follows: Low-density polyethylene resin (LDPE), grade LD 150DW; Polypropylene resin (PP), grade R520Y; Maleic anhydride-grafted polyethylene resin (PE-g-MAH), grade 4288; Metallocene polyethylene resin (m-LLDPE), grade SP1520; Sodium-based montmorillonite, with a sheet diameter of 3-8 μm and a thickness of 5-15 nm; Octaphenyl-POSS, CAS number 5256-79-1.

[0019] Example 1: Composite film I, used for manufacturing container liquid bags, has the following product structure arranged in sequence as follows: LDPE layer: The formulation is 100wt% low-density polyethylene resin, and the amount used is 10 parts by weight; First TIE layer: The formula is 100wt% maleic anhydride grafted polyethylene resin, and the amount used is 4 parts by weight. First PP layer: The formula is 100wt% polypropylene resin, and the dosage is 10 parts by weight; Second TIE layer: The formula is 100wt% maleic anhydride grafted polyethylene resin, and the amount used is 4 parts by weight. First PP-PE functional layer: The formula is 40wt% low-density polyethylene resin and 60wt% organic-inorganic hybrid high-strength filler I, with a dosage of 20 parts by weight; The third TIE layer: The formula is 100wt% maleic anhydride grafted polyethylene resin, and the amount used is 4 parts by weight. The second PP-PE functional layer: The formula is 40wt% low-density polyethylene resin and 60wt% organic-inorganic hybrid high-strength filler I, with a dosage of 20 parts by weight. Fourth TIE layer: The formula is 100wt% maleic anhydride grafted polyethylene resin, and the amount used is 4 parts by weight; Second PP layer: The formula is 100wt% polypropylene resin, and the dosage is 10 parts by weight. Fifth TIE layer: The formula is 100wt% maleic anhydride grafted polyethylene resin, and the amount used is 4 parts by weight; m-LLDPE layer: The formulation is 100wt% metallocene polyethylene resin, and the amount used is 10 parts by weight; The formulation of organic-inorganic hybrid high-strength filler I is as follows: 30wt% phenyl-POSS functionalized polyethylene, 30wt% phenyl-POSS functionalized polypropylene and 40wt% alkenyl functionalized interlaminar spacing stabilized montmorillonite. The preparation method of phenyl-POSS functionalized polyethylene is described in Experimental Example 1 below, the preparation method of phenyl-POSS functionalized polypropylene is described in Experimental Example 2 below, and the preparation method of alkenyl functionalized interlaminar spacing stabilized montmorillonite is described in Experimental Example 3 below.

[0020] Example 2: The preparation process of composite film I for manufacturing container liquid bags includes the following steps: Step 1: Preparation of organic-inorganic hybrid high-strength filler I: Under the action of Lewis acid, the phenyl functional groups in phenyl-POSS functionalized polyethylene and phenyl-POSS functionalized polypropylene undergo Friedel-Crafts alkylation reaction with the alkenyl functional groups on the surface of alkenyl functionalized interlamellar spacing stabilized montmorillonite, modifying the polyethylene and polypropylene onto the surface of montmorillonite to form a coating layer, thus preparing organic-inorganic hybrid high-strength filler I with a core-shell structure. The specific preparation steps are as follows: 3g of phenyl-POSS functionalized polyethylene, 3g of phenyl-POSS functionalized polypropylene, 4g of alkenyl functionalized interlamellar spacing stabilized montmorillonite and 0.2g of aluminum trichloride are added to a high-speed mixer and mixed evenly, and then added to a twin-screw extruder. After melt processing in the twin-screw extruder for 20min, the mixture is extruded and granulated to obtain organic-inorganic hybrid high-strength filler I. The process parameters of the twin-screw extruder are set as follows: preheating temperature 170℃, temperatures of sections 1-6 (feeding section, melting section, plasticizing section, venting section, mixing section, and extrusion section) 170℃, 180℃, 185℃, 190℃, 205℃, and 200℃ respectively, and rotation speed 400r / min. The Lewis acid can be selected from aluminum trichloride, ferric trichloride, tin tetrachloride, and zinc dichloride; in this embodiment, aluminum trichloride is selected. Step 2: Prepare the materials according to the formula of composite film I used to manufacture container liquid bags. Put the raw materials of each layer into the hopper of the eleven screw extruders of the eleven-layer co-extrusion film blow molding unit. The molten resin is combined at the die head through the distributor, and then extruded and blown through the die head (the blow-up ratio is controlled at 2.9). After cooling and winding, composite film I used to manufacture container liquid bags is prepared. The process parameters for the screw extruder corresponding to the LDPE layer and the m-LLDPE layer are set as follows: the temperatures of zones 1-3 are 120℃, 150℃, and 170℃ respectively, the flow channel temperature is 165℃, and the rotation speed is 30r / min. The process parameters for the screw extruder corresponding to the TIE layer are set as follows: the temperatures of zones 1-3 are 120℃, 150℃, and 160℃, respectively; the runner temperature is 155℃; and the rotation speed is 15r / min. The process parameters for the screw extruder corresponding to the PP layer are set as follows: the temperatures of zones 1-3 are 130℃, 160℃, and 185℃, respectively; the runner temperature is 180℃; and the rotation speed is 40r / min. The process parameters for the screw extruder corresponding to the PP-PE functional layer are set as follows: the temperatures of zones 1-3 are 150℃, 180℃, and 205℃, respectively; the runner temperature is 200℃; and the rotation speed is 60r / min.

[0021] Example 3: The composite film II used for manufacturing container liquid bags differs from the composite film I used for manufacturing container liquid bags in Example 1 only in that: organic-inorganic hybrid high-strength filler I is replaced by organic-inorganic hybrid high-strength filler II. The formulation of organic-inorganic hybrid high-strength filler II is as follows: 25wt% phenyl-POSS functionalized polyethylene, 25wt% phenyl-POSS functionalized polypropylene and 50wt% alkenyl functionalized interlaminar spacing stabilizing montmorillonite. The preparation process of composite film II used for manufacturing container liquid bags is the same as that of composite film I used for manufacturing container liquid bags in Example 2.

[0022] Example 4: The composite film Ⅲ used for manufacturing container liquid bags differs from the composite film Ⅰ used for manufacturing container liquid bags in Example 1 only in that: organic-inorganic hybrid high-strength filler Ⅲ is used instead of organic-inorganic hybrid high-strength filler Ⅰ. The formulation of organic-inorganic hybrid high-strength filler III is as follows: 20wt% phenyl-POSS functionalized polyethylene, 20wt% phenyl-POSS functionalized polypropylene and 60wt% alkenyl functionalized interlaminar spacing stabilized montmorillonite. The preparation process of composite film III used for manufacturing container liquid bags is the same as that of composite film I used for manufacturing container liquid bags in Example 2.

[0023] Comparative example: Preparation of conventional composite film: Compared with composite film I used to manufacture container liquid bags, the only difference is that the PP-PE functional layer is formulated with 100wt% low-density polyethylene resin (without using organic-inorganic hybrid high-strength filler) and the amount is 20 parts by weight.

[0024] Performance testing: I. Mechanical property tests were conducted on composite film samples used for manufacturing container liquid bags. The test results were based on the technical standard TB / T 2689.4-2018 "Railway Freight Containerization Transport Part 4: Disposable Container Liquid Bags". The test results are shown in Tables 1 and 2 below. Figure 1 As shown; Table 1 Performance test results of composite films used in the manufacture of container liquid bags

[0025] Table 2 Performance test results of composite films used in the manufacture of container liquid bags

[0026] II. Barrier performance and heat-sealing performance tests were conducted on composite film samples used in the manufacture of container liquid bags, as detailed below: (1) Barrier performance: The oxygen permeability and water vapor permeability of the samples were tested according to GB / T 1038.1-2022 "Test method for gas permeability of plastic films and sheets - Part 1: Differential pressure method" and GB / T 1037-2021 "Determination of water vapor permeability of plastic films and sheets - Cup weight gain and weight loss method". (2) Heat sealing performance: The heat sealing test was carried out on the sample. The sealing knife area was 15cm×1cm, the heat sealing temperature was 120℃, the heat sealing pressure was 0.2MPa, and the heat sealing time was 2.0s. The heat sealing strength of the heat-sealed sample was tested according to QB / T 2358-1998 "Test Method for Heat Sealing Strength of Plastic Film Packaging Bags". The test speed was 100mm / min and the clamp spacing was 50mm. The test results are shown in Table 3 below; Table 3 Performance test results of composite films used in the manufacture of container liquid bags.

[0027] A comprehensive analysis of the above experimental results leads to the following conclusions: Conclusion 1: The composite film product prepared by the present invention using the independently developed organic-inorganic hybrid high-strength filler has achieved significant improvements in mechanical properties and barrier properties compared with conventional composite films. Conclusion 2: The mechanical properties of the composite film product prepared by this invention for manufacturing container liquid bags meet the national standards, and its comprehensive performance is excellent, which has practical application value.

[0028] Experimental Example 1: Preparation of phenyl-POSS functionalized polyethylene: Free radicals are generated in low-density polyethylene resin under the action of a peroxide initiator. The alkenyl functional groups in monoalkenylphenyl-POSS react with the free radicals in low-density polyethylene resin to achieve grafting modification of low-density polyethylene resin, thus obtaining phenyl-POSS functionalized polyethylene. The specific preparation steps are as follows: First, the low-density polyethylene resin is dried in a vacuum drying oven at 50℃ for 12h. Then, 9g of dried low-density polyethylene resin, 1g of monoalkenylphenyl-POSS and 0.1g of dicumyl peroxide initiator are added to a high-speed mixer and mixed evenly. The mixture is then added to a twin-screw extruder and grafted through high-temperature melt mixing. After melt processing in a twin-screw extruder for 10min, the mixture is extruded and granulated to obtain phenyl-POSS functionalized polyethylene. The process parameters of the twin-screw extruder are set as follows: preheating temperature 150℃, temperatures of sections 1-6 (feeding section, melting section, plasticizing section, venting section, mixing section, and extrusion section in sequence) 150℃, 160℃, 170℃, 180℃, 180℃, and 175℃ respectively, and rotation speed 200r / min. The peroxide initiator can be selected from one of dicumyl peroxide, tert-butyl hydroperoxide, benzoyl peroxide, and tert-butyl peroxide; in this experimental example, dicumyl peroxide is selected. The synthesis methods of monoalkenylphenyl-POSS include, but are not limited to, the following reaction steps: Step 1: Using octaphenyl-POSS as a base material, a Friedel-Crafts alkylation reaction is carried out under the action of a Lewis acid via the alkenyl functional group of 10-undecenol and the phenyl functional group of octaphenyl-POSS. The molar ratio of octaphenyl-POSS to 10-undecenol is controlled at 1:0.92 to generate monohydroxyphenyl-POSS, whose chemical structural formula is as follows: ; The Lewis acid can be selected from aluminum trichloride, ferric chloride, tin tetrachloride, and zinc dichloride; aluminum trichloride was chosen for this experimental example. Step 2: Under the action of sulfate, the hydroxyl functional group of monohydroxyphenyl-POSS undergoes a dehydration elimination reaction to generate monoalkenylphenyl-POSS, whose chemical structural formula is as follows: ; The sulfate can be selected from aluminum sulfate, zirconium sulfate, or potassium bisulfate; this experimental example uses zirconium sulfate. The specific experimental steps for synthesizing monoalkenylphenyl-POSS are as follows: 5.2 g of octaphenyl-POSS, 0.8 g of 10-undecenol, 1.5 g of anhydrous aluminum trichloride and 50 mL of 1,2-dichloroethane were added to a three-necked flask, heated to 85 °C and stirred under reflux for 24 h, cooled to room temperature, evaporated under reduced pressure, washed with deionized water and dried to obtain monohydroxyphenyl-POSS. 3.0 g of monohydroxyphenyl-POSS, 1.8 g of zirconium sulfate and 50 mL of xylene were added to a three-necked flask, heated to 120 °C and stirred for 24 h, cooled to room temperature, evaporated under reduced pressure, washed with deionized water and dried to obtain monoalkenylphenyl-POSS; like Figure 2 As shown, the 1H NMR spectrum of monoalkenylphenyl-POSS is characterized as follows: 1H NMR (CDCl3, 400MHz) δ: 1.20-1.40 (m, 12H), 1.58-1.65 (m, 2H), 2.01-2.06 (m, 2H), 2.61-2.65 (t, 2H), 4.94-5.10 (dd, 2H), 5.74-5.84 (m, 1H), 7.16-7.54 (m, 39H).

[0029] Experimental Example 2: Preparation of phenyl-POSS functionalized polypropylene: Free radicals are generated in polypropylene resin under the action of a peroxide initiator. The alkenyl functional groups in monoalkenylphenyl-POSS react with the free radicals in low-density polyethylene resin to achieve grafting modification of polypropylene resin, thus obtaining phenyl-POSS functionalized polypropylene. The specific preparation steps are as follows: First, the polypropylene resin is dried in a vacuum drying oven at 60℃ for 12h. Then, 9g of dried polypropylene resin, 1g of monoalkenylphenyl-POSS and 0.1g of dicumyl peroxide initiator are added to a high-speed mixer and mixed evenly. The mixture is then added to a twin-screw extruder and grafted through high-temperature melt mixing. After melt processing in a twin-screw extruder for 15min, the mixture is extruded and granulated to obtain phenyl-POSS functionalized polypropylene. The process parameters of the twin-screw extruder are set as follows: preheating temperature 160℃, temperatures of sections 1-6 (feeding section, melting section, plasticizing section, venting section, mixing section, and extrusion section) 160℃, 170℃, 180℃, 190℃, 195℃, and 190℃ respectively, and rotation speed 300r / min. The peroxide initiator can be selected from one of dicumyl peroxide, tert-butyl hydroperoxide, benzoyl peroxide, and tert-butyl peroxide; in this experimental example, dicumyl peroxide is selected. The synthesis method of monoalkenylphenyl-POSS is the same as that in Experimental Example 1.

[0030] Experiment Example 3: Preparation of alkenyl-functionalized interlayer-stabilized montmorillonite: Sodium-based montmorillonite was modified by intercalation with alkenylated gemini quaternary ammonium salt. The ammonium cations of the alkenylated gemini quaternary ammonium salt first undergo ion exchange with the interlayer sodium cations of sodium-based montmorillonite, and then adsorb onto the surface of montmorillonite nanosheets through electrostatic interaction to obtain alkenyl-functionalized interlayer-stabilized montmorillonite. The specific preparation steps are as follows: 5g of sodium-based montmorillonite and 80mL of anhydrous N,N-dimethylformamide were added to a three-necked flask, sonicated for 30min, heated to 70℃ and stirred for 2h. Then, 20mL of anhydrous N,N-dimethylformamide solution containing 1g of alkenylated gemini quaternary ammonium salt was added to the three-necked flask, and the reaction was carried out at 70℃ with stirring for 6h. After filtration, the mixture was washed with anhydrous ethanol until no precipitate was detected in silver nitrate solution. After drying, alkenyl-functionalized interlayer-stabilized montmorillonite was obtained. The methods for synthesizing alkenylated gemini quaternary ammonium salts include, but are not limited to, the following reaction formulas and reaction steps: ; Step 1: An amino-enyl addition reaction occurs between the amino functional group of 3-amino-1-propanol and the alkenyl functional group of methacryloyloxyethyltrimethylammonium chloride, and the molar ratio of 3-amino-1-propanol to methacryloyloxyethyltrimethylammonium chloride is controlled to be 1:2.06 to generate the hydroxyammonium chloride monomer. Step 2: A nucleophilic substitution reaction occurs between the hydroxyl functional group of the ammonium hydroxychloride monomer and the acyl chloride functional group of 10-undecenoyl chloride, and the molar ratio of ammonium hydroxychloride monomer to 10-undecenoyl chloride is controlled to be 1:1.03 to generate an alkenylated gemini quaternary ammonium salt. The specific experimental steps for synthesizing alkenylated gemini quaternary ammonium salts are as follows: 0.7 g of 3-amino-1-propanol and 10 mL of anhydrous N,N-dimethylformamide were added to a three-necked flask and stirred at room temperature until completely dissolved. Then, 40 mL of anhydrous N,N-dimethylformamide solution containing 4.1 g of methacryloyloxyethyltrimethylammonium chloride was added to the three-necked flask and stirred at room temperature for 30 min. The mixture was then heated to 60 °C and stirred for 4 h. After cooling to room temperature, the mixture was evaporated under reduced pressure and dried to obtain the hydroxyammonium chloride monomer. 2.4 g of ammonium hydroxide monomer and 20 mL of anhydrous N,N-dimethylformamide were added to a three-necked flask and stirred at room temperature until completely dissolved. Under nitrogen protection, 10 mL of anhydrous N,N-dimethylformamide solution containing 1.0 g of 10-undecenoyl chloride was added to the three-necked flask. The mixture was heated to 40 °C and stirred for 6 h. After cooling to room temperature, 1.5 mL of 5 wt% sodium carbonate aqueous solution was added dropwise. The mixture was then rotary evaporated under reduced pressure, washed with deionized water, and dried to obtain an alkenylated gemini quaternary ammonium salt. like Figure 3 As shown, the 1H NMR characterization of the alkenylated gemini quaternary ammonium salt is as follows:1 H NMR(CDCl3,400MHz)δ:1.17-1.19(d,6H),1.25-1.42(m,12H),1.82-1.89(m,2H),2.01-2.06(m,2H),2.29-2.32(t,2H),2.49-2.58(m,2H),2.62-2.65(t,2H),2.79-2.81(d,4H),3.36(s,18H),3.71-3.74(t,4H),4.07-4.11(t,2H),4.35-4.39(t,4H),4.95-5.10(dd,2H),5.74-5.84(m,1H)。

Claims

1. A composite film for manufacturing container liquid bags, characterized in that, The product structure of the composite film is: LDPE layer / TIE layer / PP layer / TIE layer / PP-PE functional layer / TIE layer / PP-PE functional layer / TIE layer / PP layer / TIE layer / m-LLDPE layer; The LDPE layer is formulated with 100wt% low-density polyethylene resin, and the amount used is 5-15 parts by weight. The TIE layer is formulated with 100wt% maleic anhydride-grafted polyethylene resin, and the dosage is 1-5 parts by weight. The PP layer is formulated with 100wt% polypropylene resin, and the dosage is 5-15 parts by weight. The PP-PE functional layer is formulated with 30-50 wt% low-density polyethylene resin and 50-70 wt% organic-inorganic hybrid high-strength filler, with a dosage of 15-25 parts by weight. The formulation of the organic-inorganic hybrid high-strength filler is as follows: 20-30 wt% phenyl-POSS functionalized polyethylene, 20-30 wt% phenyl-POSS functionalized polypropylene, and 40-60 wt% alkenyl functionalized interlamellar spacing stabilizing montmorillonite; wherein, the phenyl-POSS functionalized polyethylene is obtained by grafting monoalkenyl phenyl-POSS onto the polyethylene backbone via a free radical addition reaction; the phenyl-POSS functionalized polypropylene is obtained by grafting monoalkenyl phenyl-POSS onto the polypropylene backbone via a free radical addition reaction; and the alkenyl functionalized interlamellar spacing stabilizing montmorillonite is obtained by intercalating sodium-based montmorillonite with alkenylated gemini quaternary ammonium salt via an ion exchange reaction. The chemical structural formula of the alkenylated gemini quaternary ammonium salt is: ; The chemical structural formula of monoalkenylphenyl-POSS is: ; The m-LLDPE layer is formulated with 100wt% metallocene polyethylene resin, and the amount used is 5-15 parts by weight.

2. The composite film for manufacturing container liquid bags according to claim 1, characterized in that, The thickness of the composite film is 130-180 μm.

3. The composite film for manufacturing container liquid bags according to claim 1, characterized in that, The mass ratio of alkenylated gemini quaternary ammonium salt to sodium-based montmorillonite in the alkenyl-functionalized interlamellar spacing stabilized montmorillonite is 1:(3-8).

4. The composite film for manufacturing container liquid bags according to claim 3, characterized in that, The sodium-based montmorillonite flakes have a diameter of 3-8 μm and a thickness of 5-15 nm.

5. The composite film for manufacturing container liquid bags according to claim 1, characterized in that, The mass ratio of monoalkenylphenyl-POSS to polyethylene in the phenyl-POSS functionalized polyethylene is 1:(8-10); The mass ratio of monoalkenylphenyl-POSS to polypropylene in the phenyl-POSS functionalized polypropylene is 1:(8-10).

6. The process for preparing the composite film for manufacturing container liquid bags according to any one of claims 1-5, characterized in that, Includes the following steps: Step 1: Synthesize monoalkenylphenyl-POSS, and then use monoalkenylphenyl-POSS to functionalize and modify polyethylene and polypropylene in sequence to obtain phenyl-POSS-functionalized polyethylene and phenyl-POSS-functionalized polypropylene. Alkenylated gemini quaternary ammonium salts were synthesized, and sodium-based montmorillonite was functionalized by the alkenylated gemini quaternary ammonium salts to obtain alkenylated functionalized interlamellar spacing stabilized montmorillonite. Under the action of Lewis acid, the phenyl functional groups in phenyl-POSS functionalized polyethylene and phenyl-POSS functionalized polypropylene undergo Friedel-Crafts alkylation reaction with the alkenyl functional groups on the surface of alkenyl functionalized interlaminar spacing stabilized montmorillonite, and polyethylene and polypropylene are grafted onto the surface of montmorillonite to obtain an organic-inorganic hybrid high-strength filler. Step 2: Prepare the materials according to the formula of the composite film. Put the raw materials of each layer into the hoppers of the eleven screw extruders of the eleven-layer co-extrusion film blow molding unit. The molten resin is combined at the die head through the distributor, extruded and blown by the die head, cooled and wound up to prepare the composite film for manufacturing container liquid bags.

7. The preparation process of the composite film for manufacturing container liquid bags according to claim 6, characterized in that, The preparation method of the alkenylated gemini quaternary ammonium salt is as follows: The amino-enyl addition reaction occurs through the amino functional group of 3-amino-1-propanol and the alkenyl functional group of methacryloyloxyethyltrimethylammonium chloride, and the molar ratio of 3-amino-1-propanol to methacryloyloxyethyltrimethylammonium chloride is controlled to be 1:2.05-2.09 to generate hydroxyammonium chloride monomer. A nucleophilic substitution reaction is carried out between the hydroxyl functional group of ammonium hydroxychloride monomer and the acyl chloride functional group of 10-undecenoyl chloride, and the molar ratio of ammonium hydroxychloride monomer to 10-undecenoyl chloride is controlled to be 1:1.01-1.05 to generate an alkenylated gemini quaternary ammonium salt.

8. The preparation process of the composite film for manufacturing container liquid bags according to claim 6, characterized in that, The preparation method of the monoalkenylphenyl-POSS is as follows: Under the action of Lewis acid, Friedel-Crafts alkylation reaction occurs through the alkenyl functional group of 10-undecenol and the phenyl functional group of octaphenyl-POSS, and the molar ratio of octaphenyl-POSS to 10-undecenol is controlled to be 1:0.91-0.95 to generate monohydroxyphenyl-POSS; Under the action of sulfate, the hydroxyl functional group of monohydroxyphenyl-POSS undergoes a dehydration elimination reaction to generate monoalkenylphenyl-POSS.

9. The preparation process of the composite film for manufacturing container liquid bags according to claim 8, characterized in that, The Lewis acid is one of aluminum trichloride, ferric trichloride, tin tetrachloride, and zinc dichloride.

10. The preparation process of the composite film for manufacturing container liquid bags according to claim 8, characterized in that, The sulfate is one of aluminum sulfate, zirconium sulfate, and potassium bisulfate.

Citation Information

Patent Citations

  • High-barrier polyethylene film easy to tear linearly and preparation process thereof

    CN119058202A

  • Eleven-layer co-extruded film containing PE-PA-EVOH material, preparation method and application of eleven-layer co-extruded film in container liquid bag

    CN119078332A

  • Bio-based gemini quaternary ammonium salt compound as well as preparation method and application thereof

    CN119661481A

  • Preparation of n-substituted 6,7-methylenedioxy-4-quinolone derivatives

    GB1324332A

  • Collapsible fluid vessels

    WO1998013276A1

Cited By

  • PE (Poly Ethylene) heat-shrinkable packaging film

    CN122188264A